Ancestral Pueblo and Historic Ute Rock Art, and Euro-American Inscriptions in the Canyons of the Ancients National Monument, Colorado, USA - Radoslaw Palonka; Polly Schaafsma; Katarzyna M. Ciomek (Arts, 2025)
In the central Mesa Verde region, rock art occurs on canyon walls and on boulders that are frequently associated with other archaeological remains. Moreover, rock art, together with architecture and pottery, is actually a primary source of archaeological information about the presence of various cultures in the area. It includes paintings and petroglyphs of Ancestral Pueblo farming communities, images and inscriptions made by post-contact Ute and possibly Diné (Navajo) people as well as historical inscriptions of the early Euro-Americans in this area. This paper presents the results of archaeological investigations at four large rock art sites from Sandstone Canyon, southwestern Colorado, within the Canyons of the Ancients National Monument (CANM). Methods of rock art recording included advanced digital photography, photogrammetry, terrestrial laser scanning (TLS), hand tracing, and consultations with members of indigenous societies and rock art scholars. Geophysics and sondage excavations were conducted at one site revealed important information about archaeology, environment, and geology of the area. Analysis of rock art and other material evidence aims to help reconstruct and understand the mechanisms and nature of cultural changes, migrations, and human–environmental interactions and later cross-cultural contacts between indigenous peoples and Anglo-American ranchers and settlers in southwestern Colorado and the US Southwest.